Implementasi pembelajaran fiqih muamalah dalam penguatan nilai pendidikan kewirausahaan di Pondok Pesantren Al-Islam Darul Falah Sragen - Lilis Suryanto; Mulyanto Abdullah Khoir (At Turots: Jurnal Pendidikan Islam, 2023)
This research aims to explore the implementation of muamalah fiqh learning in strengthening entrepreneurial values in Al-Islam Darul Falah Sragen Islamic Boarding School. The research method used is qualitative with data collection techniques in the form of observation, interviews, and documentation study. The results showed that muamalah fiqh learning can effectively strengthen entrepreneurial values among students. Muamalah fiqh learning encourages students to have a better understanding of the principles of Islamic business ethics and provides a strong foundation for the development of entrepreneurial skills. In this regard, the role of teachers is crucial in delivering muamalah fiqh material in a way that is interesting and relevant to the daily lives of students.